PENANGANAN PEMBIAYAAN BERMASALAH PADA PEMBIAYAAN MURABAHAH DI KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH (KSPPS) KHAIRU UMMAH LEUWILIANG KABUPATEN BOGOR PADA MASA PANDEMI COVID-19 - Yuspardiansyah, Ade; Thantawi, Tubagus Rifqy; Mursyidah, Azizah (SAHID BANKING JOURNAL, 2023)
This research aims to determine the causes of financing problems in murabahah contract financing during the Covid-19 pandemic. Then to find out the strategies used to handle problematic financing during the Covid-19 pandemic. Furthermore, to find out the efforts made by KSPPS Khairu Ummah Leuwiliang Bogor Regency in providing policies to murabahah contract financing customers who are affected by the Covid-19 pandemic. The data analysis method or technique used for this research is qualitative descriptive analysis techniques using the SWOT analysis approach. Based on the results of this research, the factors that cause problematic financing are internal factors such as weaknesses in analyzing financing, lack of supervision and monitoring of customer capabilities, and negligence by officers in setting risk standards when providing financing during the Covid-19 pandemic. External factors occur in the members themselves because they experience declining business conditions, and there is no good faith on the part of the members in delaying installment payments. The efforts provided by KSPPS Khairu Ummah Leuwiliang Bogor Regency to customers who experienced bad credit during the Covid-19 pandemic were a stay strategy and a phase out strategy.